Transformation of mammalian fibroblasts and macrophages in vitro by a murine retrovirus encoding an avian v-myc oncogene. - Vennström, B (1984)
A murine retrovirus which expresses the avain v-myc OK10 oncogene was constructed. The virus, denoted MMCV, readily transforms fibroblasts of established lines, such as mouse NIH/3T3 and rat 208F cells, to anchorage-independent growth in agarose. The virus also transforms primary mouse cells: (i) virus-infected macrophages are induced to form large colonies in semi-solid media, and can easily be expanded into mass cultures; (ii) MMCV-infected fibroblastic cells from mouse limb buds undergo morphological transformation and grow in semi-solid medium. MMCV thus transforms both mouse fibroblastic cells and macrophages in vitro, in a fashion similar to the v-myc-containing avian viruses in chicken cells. The possibility of introducing a transforming myc gene into mammalian cells by virus infection provides a novel approach for studying the mechanism of myc transformation in cells from many lineages.